2021
DOI: 10.12998/wjcc.v9.i21.5812
|View full text |Cite
|
Sign up to set email alerts
|

Soluble programmed death-1 is predictive of hepatitis B surface antigen loss in chronic hepatitis B patients after antiviral treatment

Abstract: BACKGROUND Hepatitis B surface antigen (HBsAg) loss, a functional cure in patients with chronic hepatitis B (CHB) undergoing antiviral therapy, might be an ideal endpoint of antiviral treatment in clinical practice. The factors that contribute to the functional cure remain unclear, and the predictors of functional cure are worth exploring. The concentration and kinetics of soluble programmed death-1 (sPD-1) in patients with CHB may play an important role in elucidating the immune response associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Consistent with a small scale study that high sPD-1 levels were predictive of HBsAg loss during treatment. 20 In the present study, detectable sPD-1 at EOT was negatively associated with clinical relapse and positively associated with subsequent HBsAg loss. The AUROC values for EOT sPD-1 were not perfect to predict clinical relapse and HBsAg loss, at 0.65 and 0.70, respectively.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Consistent with a small scale study that high sPD-1 levels were predictive of HBsAg loss during treatment. 20 In the present study, detectable sPD-1 at EOT was negatively associated with clinical relapse and positively associated with subsequent HBsAg loss. The AUROC values for EOT sPD-1 were not perfect to predict clinical relapse and HBsAg loss, at 0.65 and 0.70, respectively.…”
Section: Discussionsupporting
confidence: 54%
“…15–17 However, very little research has assessed the concentration and kinetics of sPD-1 during chronic HBV infection. 18–22 Recently, Tan et al 20 showed that sPD-1 expression is associated with functional cure during NA therapy. However, the potential value of sPD-1 in patients with NA discontinuation is not well understood.…”
Section: Introductionmentioning
confidence: 99%